Referential analysis of discharge and salinity data in Shatt Al-Arab River - Al-Mahmood, Hassan Khaleel H. (Iraqi Journal of Aquaculture, 2021)
The space-time changes of waters could be considered the basis for research in in applied hydrology. The purpose of this science is to develop scientific and logical explanations of hydrological changes and to gain an understanding of the interrelationships between them. The present study aims at developing a database of river discharge and salinity concentration in the Shatt Al-Arab river (i.e., for selected sites) and the research was based on analysis of previous reference data and research measures that included data recorded for discharge volume and water quality during the period from 1978 to 2017 to reveal change in water nutrition size and effects in salinity. The study showed a link between the two rivers' running system, the amount of Shatt al Arab discharge and the quality of its water with the emergence of a temporal effect of the Karon River in the southern part of the stream, a link between decreasing discharge and salinity, changing salinity does not take a single pattern in all locations or periods studied, and water discharge gradually showed a decrease after the 1990s, and continued to reach its peak during the two years (2008-2009 and 2014-2015), The study recommends the quantity and quality of water coming to Shatt al-Arab should be continuously reinforced, evaluation plans should be made from time to time, and hydraulic systems placed on some of the entrances of Shatt al-Arab.